The Public Perception of Early Warning System in Forest Fire Prevention Efforts Perum Perhutani KPH Pasuruan East Java - Ati Dwi Nurhayati; Haridha Anindita; Handian Purwawangsa (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Most of forest and land fire in Indonesia caused by human activities therefore it is imfortant to prevent it by conducting researh to identify the factor based on perception level of people. To have know ledge about forest and land fire factors, can help to determine fire danger rating of one specific area. As a result, we can design effective early warning system in preventing forest & land fire. The study shows that the perception level of people early warning system is at low degree. Kunjoro Wesi and Wotanmas Jedong Village have 93,30% and Sumberrejo Village has 63,30% of respondent with no knowledge on EWS. While Tambalsari village considered to have middle level of perception, with 50% of respondent have know ledge on EWS. According to Spearmen formal education has a positive correlation with perception level of EWS on all four village. So the level of formal education has a significant contibution for people knowledge.